Laser-Induced Charge Transfer Under Crossed-Beam Conditions: Application to the Na + I2 → Na + + I2− System. Issue 1 (1992) - Bañares, L.; Skowronek, S.; Perdiguero, C.; Ureña, A. González
Abstract : A crossed-beam charge transfer study was carried out for the Na(3 2 P3/2, 1/2 ) + I2 → Na + +I 2 − system using laser excitation of the Na atom. The excitation functions were measured for the title reaction, searching for spin orbit effects. A common energy threshold of E 0 ≃0.23eV was found for both processes. In addition, similar post-threshold laws for each spin-orbit state indicate the absence of such effects over the low collision energy range.